Effective Governance to Develop Creative Quarters: Three Case Studies from Germany - Lauderbach, Martina (Quaestiones Geographicae, 2012)
As the positive economic and social impacts of the creative economy on regions are evident, many regions and local policy makers aim to attract creative industries and creative people by offering adequate spaces and framework conditions (Musterd & Murie 2010). Beside other efforts, creative quarters are initiated artificially by top-down governance. Based on the assumption that creatives (bohemians, core of the creative class) need a certain amount of autonomy and do not want to be instrumentalised, initiating creative quarters top-down seems to be difficult. This paper analyses different ways of governance to develop creative quarters in the range of top-down, bottom-up and co-governance. By reference to three quarters (located in the Ruhr area, Germany) which have been developed by different ways of governance, the research derives ideal governance structures and processes to develop creative quarters considering practical opportunities and limitations.